El control previo y la contabilidad gubernamental en las instituciones públicas del distrito de Iquitos, 2021 - Correa Mosquera, Fabiola (2022)
The current study is titled "Prior Control and Government Accounting in Public Institutions of the Iquitos district, 2021". The general objective is to know the contribution of the prior control in the government accounting of the public institutions of the Iquitos district. The research methodology has a non-experimental, descriptive and explanatory design, and oriented to 52 public institutions, validated surveys and observations were used for data collection, to later process and publish the data. Finally, from the critical value obtained, we can determine that the impact that prior control has on the accounting area of public institutions in Iquitos is positive. In terms of performance, 100% of those who responded to the surveys consider prior control as a fundamental factor in the administrative area, mainly for decision-making and avoiding administrative errors.